2020
DOI: 10.1155/2020/6096024
|View full text |Cite
|
Sign up to set email alerts
|

Rolling Bearing Fault Diagnosis Based on Adaptive Multiparameter-Adjusting Bistable Stochastic Resonance

Abstract: The weak-signal detection technologies based on stochastic resonance (SR) play important roles in the vibration-based health monitoring and fault diagnosis of rolling bearings, especially at their early-fault stage. Aiming at the parameter-fixed vibration signals in practical engineering, it is feasible to diagnose the potential rolling bearing faults through adaptively adjusting the SR system parameters, as well as other generalized parameters such as the amplitude-transformation coefficient and scale-transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…In addition, more and more methods to improve LBP have emerged in recent years, such as local maximum edge cooccurance patterns, 12 local gradient patterns, 13 scale-adaptive local binary patterns, 14 local directional extrema number pattern (LDIRENP), 15 graph based structure binary pattern, 16 and other variants. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Ernst Weber, a 19th century experimental psychologist, observed that the ratio of incremental threshold to background intensity is a constant. This relationship is known as Weber's law and can be expressed as E Q -T A R G E T ; t e m p : i n t r a l i n k -; e 0 0 1 ; 1 1 6 ; 4 0 7…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, more and more methods to improve LBP have emerged in recent years, such as local maximum edge cooccurance patterns, 12 local gradient patterns, 13 scale-adaptive local binary patterns, 14 local directional extrema number pattern (LDIRENP), 15 graph based structure binary pattern, 16 and other variants. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Ernst Weber, a 19th century experimental psychologist, observed that the ratio of incremental threshold to background intensity is a constant. This relationship is known as Weber's law and can be expressed as E Q -T A R G E T ; t e m p : i n t r a l i n k -; e 0 0 1 ; 1 1 6 ; 4 0 7…”
Section: Introductionmentioning
confidence: 99%
“…In addition, more and more methods to improve LBP have emerged in recent years, such as local maximum edge cooccurance patterns, 12 local gradient patterns, 13 scale-adaptive local binary patterns, 14 local directional extrema number pattern (LDIRENP), 15 graph based structure binary pattern, 16 and other variants 17 31 …”
Section: Introductionmentioning
confidence: 99%
“…Unlike the conventional denosing methods, stochastic resonance (SR) is a method that reduces noise interference by transferring noise energy to fault signals. rough using a nonlinear system, part of the noise energy is transferred to the low-frequency signal, and the resonance of the weak signal submerged in the noise is strengthened so as to reduce the noise interference and extract the signal features effectively [30][31][32]. In order to solve the feature extraction and fault diagnosis of rolling bearings under a large amount of noise, Li and Shi [33] proposed a signal processing method that combined EEMD and adaptive stochastic resonance and applied it to the rolling bearing vibration signal, effectively enhancing the weak fault features and extracting them.…”
Section: Introductionmentioning
confidence: 99%
“…This method can effectively detect weak signal characteristics hidden in strong noise. Z. H. Lai et al [30] proposed an adaptive multi-parameter tuned stochastic resonance method for bistable systems based on particle swarm optimization algorithm, which generates optimal SR output by adaptively adjusting multiple parameters to achieve fault feature extraction and further fault diagnosis of rolling bearings. However, the cascaded bistable stochastic system involves multiple model parameters, the system parameters are difficult to adjust, the adjustment process is time-consuming, and engineers with insufficient experience may be unable to obtain the optimal SR output.…”
Section: Introductionmentioning
confidence: 99%